Coping Mechanisms for Food Insecurity among Rural Households in Bitereko Sub-County, Mitooma District: Convergent Parallel Mixed-Methods Design - Ngabirano, Augustino; Nabitandikwa, Catherine; Neeza, Timothy; Igwe, Mathew Chibunna (International Journal of Research and Innovation in Social Science, 2024)
Food insecurity is a multifaceted global health concern, causing poor health in low- and middle-income countries, especially in rural sub-Saharan Africa. This study was done to assess causes of food insecurity, explore coping strategies and the effect of environmental factors and locally accessible resources on the food situation in Bitereko Sub- County, Mitooma district, Uganda. This article’s empirical analysis is predicated on data collected on thirty-two households from Bitereko Sub- County between September and October 2018 which were selected using stratified sampling technique. Focus group discussions, key informant interviews and a semi-structured questionnaire were used for data collection. Descriptive analysis was done using IBM SPSS version 20 while qualitative (thematic and content) analysis was conducted manually. The study findings show that population increase and land degradation is the main cause of food shortage in the area. Banana was reported (100%) by both genders to be the major food crop relied upon by the households. Reducing the number of meals (40.62%) was the main coping strategy to food insecurity. Diversification into non-farm activities and agricultural diversification are two main livelihood adjustment strategies that have emerged in the area in relation to environmental factors and locally available resources. The study findings indicate that gender, age group and education level significantly influenced the food situation in a given household. Households whose heads were male were more likely to experience food insecurity as compared to the females χ2 (1, N = 32) = .002, p = .041. Households with respondents aged between 20 – 29 years were less likely to experience food insecurity than those aged between 30 – 39 years χ2 (5, N = 32) = 16.09, p = .007. Whereas respondents who had attained up to primary level of education were more likely to experience food insecurity in their households as compared to those who had never been to school χ2 (4, N = 32) = 15.71, p = .003.